Dynamic Carotid Doppler Indices Predict Fluid Responsiveness in PostOperative Cardiac Patients - Mohamed Hamdi Saleh; Mohamed Samir Ali; Khaled Abdel Azem Shoukry; Kamel Abdelaziz Abdullah (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: While it has been established that carotid blood flow (CBF) correlates significantly with stroke volume index (SVI), the accuracy of carotid flow Doppler indices in assessing fluid responsiveness in post-operative cardiac patients remains unknown.Aim: to see if Fluid Responsiveness Can Be Predicted Using Dynamic Carotid Doppler Indices After Cardiac Surgery.Patients and Methods: Research was done at Cairo University's critical care unit, which is part of the medical school. There were 70 patients admitted to the Surgical Intensive Care Unit in a row. Patients were divided into two groups: those who responded and those who did not.Results: Δ total carotid flow, Δ systolic carotid flow, Δ corrected carotid flow time, and Δ HR % change were significantly higher among responder’s group than non-responder (16.47±3.73, 13.18±4.19, and 14.00±5.22 vs 8.44±2.74, 5.68±3.33, and 10.16±5.12, p value: